Indonesian History Subject for Peace Education Through the Integration of Local History - Wafiyatu Maslahah; Arif Wahyu Hidayat (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This research aimed to describe Indonesian history subject and identify peace education within Indonesian history subject through the integration of local history. This research was qualitative research with phenomenology approach. The data were collected though interview, observation and documentation. The research was taken place in Madrasah Aliyah Assalam Jambewangi, Selopuro District, Blitar Regency. The validity of the research was measured by triangulation. The data analysis technique used were data reduction, data presentation, and conclusion. The result showed that: 1) the teacher made lesson plan as teaching apparatus. The learning materials were delivered by lecturing and taken from textbook and worksheet. The teacher did not use any teaching media. The purpose of Indonesia history was not explained by the teacher. The students considered it as boring lesson for it was like a bedtime story time. 2) Peace education could not be implemented because the teacher had not taught ideally. Peace education can only be implemented when the teacher is creative and innovative, as well as raising local history.